THE CASE OF Q-WAVE MYOCARDIAL INFARCTION IN A 35-YEARS-OLD FEMALE - A. B. Tashtanaliev (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article presents a case of Q-wave myocardial infarction, in a young woman of 35 years old. The patient complained. of pains not typical for angina pectoris. Therefore, the initial diagnosis was incorrect. After 3 months myocardial infarction, of cicatrization, stage was diagnosed. For definition, of further tactics of treatment we used, coronary angiography and recommended, stenting of critical stenosis on left anterior descending artery. For prophylactics of this case electrocardiography should, be routinely used, in all the cases of pain in the neck and. thorax in young women.